The extracellular matrix glycoprotein ADAMTSL2 is increased in heart failure and inhibits TGFβ signalling in cardiac fibroblasts - Karoline B. Rypdal (Nature Portfolio, 2021)
Abstract Fibrosis accompanies most heart diseases and is associated with adverse patient outcomes. Transforming growth factor (TGF)β drives extracellular matrix remodelling and fibrosis in the failing heart. Some members of the ADAMTSL (a disintegrin-like and metalloproteinase domain with thrombospondin type 1 motifs-like) family of secreted glycoproteins bind to matrix microfibrils, and although their function in the heart remains largely unknown, they are suggested to regulate TGFβ activity. The aims of this study were to determine ADAMTSL2 levels in failing hearts, and to elucidate the role of ADAMTSL2 in fibrosis using cultured human cardiac fibroblasts (CFBs). Cardiac ADAMTSL2 mRNA was robustly increased in human and experimental heart failure, and mainly expressed by fibroblasts. Over-expression and treatment with extracellular ADAMTSL2 in human CFBs led to reduced TGFβ production and signalling. Increased ADAMTSL2 attenuated myofibroblast differentiation, with reduced expression of the signature molecules α-smooth muscle actin and osteopontin. Finally, ADAMTSL2 mitigated the pro-fibrotic CFB phenotypes, proliferation, migration and contractility. In conclusion, the extracellular matrix-localized glycoprotein ADAMTSL2 was upregulated in fibrotic and failing hearts of patients and mice. We identified ADAMTSL2 as a negative regulator of TGFβ in human cardiac fibroblasts, inhibiting myofibroblast differentiation and pro-fibrotic properties.